Measuring and Analyzing the Impact of Public Expenditure on Inflation Rates in Iraq (2004-2022) (Raparin Journal of Humanities (RJH), 2025)
Public expenditures are the main element in influencing indicators of economic stability, as public expenditures affect economic growth by increasing or decreasing production, through their impact on increasing demand, The research aims to analyze the impact of public spending on economic inflation rates in the Iraqi economy during the period (2004 - 2022) and the use of time series to express the nature of the relationship between the variables of the study by estimating and analyzing the relationship in the applied side in which the ARDL model was used.The study employs descriptive analysis and econometric methods using (ARDL) approach to assess these factors. The results reveal that public expenditures, GDP, and the state of the war on terrorism have strong effects on inflation rates in the short term. However, the impact of exchange rate fluctuations on inflation is found to be very weakThe impact of gross national product (GNP) on inflation rates remains strong in the long term. However, the effect of public expenditures has turned negative, which can be attributed to the nature of the Iraqi rentier economy. On the other hand. This research suggests that Iraq needs to implement a balanced fiscal policy and focus on government public expenditures.